IDENTIFICATION OF PEST AND DISEASE ATTACKS ON CORN PLANTS IN MAGUWOHARJO VILLAGE FIELDS - Talitha Rojwa Azri; Ananta Septia Santana; Dewanata Abdhe Wijaya; Sabrina Atika Putri; George Nathaniel Angkasa Putra Rostila Asmara; Naufaldi Adicandra (Agrofarm: Jurnal Agroteknologi, 2025)
Corn (Zea mays L.) is one of the most important cereal crops in the world, after wheat and rice. Corn cultivation often faces serious challenges due to pest and disease attacks that cause significant losses for farmers. This study aimed to identify the incidence and damage intensity caused by major pests (fall armyworm and grasshopper) and diseases (leaf blight and downy mildew) in corn fields at Maguwoharjo Village. A quantitative survey using a simple random sampling method with diagonal clustering was applied to 500 corn plants, representing 10% of the population. Observations were made weekly from 6 to 10 weeks after planting (WAP), recording symptoms and calculating infestation levels to better inform targeted pest and disease management strategies. The results of the study show that grasshoppers and armyworms are the main pests, with an incidence rate of 70% and an attack intensity of 40% for grasshoppers, and an incidence rate of 50% with an attack intensity of 17% for armyworms. In addition, leaf blight and smut diseases also have significant incidence rates, reaching 100% and 84%, with attack intensities of 47% and 35%, respectively. This research provides important information for the development of integrated control strategies to reduce losses due to pest and disease attacks on corn crops.